2021
DOI: 10.3390/pathogens10080931
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of G6PD Genotypes in Different Ethnic Groups Residing in Saharan and Sahelian Zones of Mauritania

Abstract: Plasmodium vivax malaria is endemic in Mauritania. Individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency may develop acute hemolytic anemia when exposed to 8-aminoquinoline antimalarial drugs, which are indispensable for a complete cure. The prevalence of G6PD allelic variants was assessed in different ethno-linguistic groups present in Mauritania. A total of 996 blood samples (447 males and 549 females; 499 white Moors and 497 individuals of black African ancestry) were collected from febrile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 48 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Our preliminary study using PCR-RFLP showed that 6.3% of Mauritanian males of both Arab-Berber and black African ancestries have the African-type G6PD A 2 genotype (G6PD A 2(202) , G6PD A 2 Santamaria, and G6PD A 2 Betica-Selma), whereas the Mediterranean-type genotype was not observed. 42 In Mali and Senegal, two countries that share a common border with Mauritania to the east and south, the African-type G6PD A 2 genotype has been reported in 2.2% to 10% of males. 43,48,49 In the countries north of Mauritania, the prevalence of a G6PD enzyme deficiency in the male population has been reported to be 3.2% in Algeria, mostly because of autochthonous variants predominated by the Kabyle type, but also resulting from the Mediterranean-type genotype as well as the African-type A 2 in a minority of persons with black African ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our preliminary study using PCR-RFLP showed that 6.3% of Mauritanian males of both Arab-Berber and black African ancestries have the African-type G6PD A 2 genotype (G6PD A 2(202) , G6PD A 2 Santamaria, and G6PD A 2 Betica-Selma), whereas the Mediterranean-type genotype was not observed. 42 In Mali and Senegal, two countries that share a common border with Mauritania to the east and south, the African-type G6PD A 2 genotype has been reported in 2.2% to 10% of males. 43,48,49 In the countries north of Mauritania, the prevalence of a G6PD enzyme deficiency in the male population has been reported to be 3.2% in Algeria, mostly because of autochthonous variants predominated by the Kabyle type, but also resulting from the Mediterranean-type genotype as well as the African-type A 2 in a minority of persons with black African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was 100% successful in two other PCR plates, and genotyping by PCR-RFLP and sequencing was successful with the same samples as those in the first PCR plate, ruling out template quality as the possible cause of failure. 42 Moreover, the earlier 2013 protocol (version 1.3) of the manufacturer recommended an annealing temperature of 60 C. Indeed, for all samples in two PCR plates, lowering the annealing temperature to 60 C resulted in clearly visible bands in agarose gel electrophoresis. This observation implies that some test runs with control samples are required in each laboratory before PCR amplification in PCR plates is performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations